An atomistic modeling survey of the shear strength of twist grain boundaries in aluminum. (May 2015) - Bomarito, G.F.; Lin, Y.; Warner, D.H.
Abstract : A computational survey of the shear strength of 343 unique grain boundaries was performed. For each boundary, the strength was surveyed as a function of shear direction. The results suggest that: (1) the shear strength cannot be comprehensively predicted by common grain boundary descriptors, (2) the shear strength depends significantly and simply on shear direction due to the faceted geometry of boundary planes, and (3) grain boundary shear strengths in an ordinary material can be represented by a simple statistical distribution.